Improving The Quality Of Human Resources In Banua Anyar Culinary Tourism Village Through Sapta Pesona Tourism Awareness Socialization - Ismi Rajiani; Sutarto Hadi; Mutiani Mutiani; Ahmad Hapis Ansari; Muhammad Ryan Dwi Adityas; Nur Laili As Syifa (Universitas Lambung Mangkurat, 2023)
Good and sustainable Pokdarwis management will improve the source of economic income for local communities and the government area; with this development, it is hoped that many people will feel the impact. The service is carried out with four stages of activity, namely: 1) initial observation; 2) Analysis of Pokdarwis implementing activities; 3) Extension activities; and 4) Training related to the promotion of tourist destinations. The service was held on 01 – 24 July 2023. The results of this activity describe that Pokdarwis Ceria's space is focused on culinary tourism. KUliner is an aspect that supports tourism, although other potentials, such as the nature and culture of an area, are also packaged into a tourist attraction. Community service is expected to increase public understanding of the Sapta Pesona conception. Thus, strengthening the identity of Pokdarwis, Banua Anyar Village, to improve community welfare through the Culinary Tourism Area promotion program. It is because culinary tourism is an activity carried out by many people in the field of food needs for entertainment